Pengembangan Potensi Ekowisata Berbasis Masyarakat Pada Hutan Mangrove Kampung Sejahtera Kota Bengkulu - Safrianti, Sintia; Yunita, Mirna; Puspita, Veny; Pratama, Fadly Wahyu; Ramadhani, Rahmad; Pangestu, Heru Edlifilyas (STMIK Royal, 2025)
This community service activity was carried out in the Kampung Sejahtera Mangrove Forest, Bengkulu City and partnered with POKDARWIS 212. The Kampung Sejahtera mangrove forest is located in Kampung Melayu District, Bengkulu City. This community service aims to solve priority problems that exist in partners, namely: Partners and the community still do not understand the positive impact of the existence of mangrove forest ecotourism on economic improvement; Lack of knowledge of the community around the mangrove forest ecotourism environment regarding the preservation and maintenance of mangrove forests; Lack of integrated information and promotion by mangrove forest POKDARWIS 212 partners. Community service activities are carried out with an initial observation stage through a pre-activity questionnaire, followed by an implementation stage with socialization and training, and the next stage conducts an evaluation. The outputs produced in this community service are: The formation of the 212 mangrove forest POKDARWIS cooperative; The formation of a Joint Business Group (KUBE) of MSMEs from the community around mangrove ecotourism; The existence of 3 mangrove-based creative products; The reforestation of mangrove forests that will be cultivated in the mangrove forest ecotourism of the prosperous village; The existence of an integrated website as a promotional forum; and 6) The existence of signboards as information media.Keywords: ecotourism; community based; mangrove forest of the prosperous village; bengkulu cit Abstrak: Kegiatan pengabdian kepada masyarakat ini dilakukan di Hutan Mangrove Kampung Sejahtera Kota Bengkulu dan bermitra bersama POKDARWIS 212. Hutan mangrove Kampung Sejahtera ini berada di Kecamatan Kampung melayu, Kota Bengkulu. Pengabdian kepada masyarakat ini bertujuan untuk memecahkan permasalahan prioritas yang ada pada mitra, yaitu: Mitra dan masyarakat masih belum memahami dampak positif keberadaan ekowisata hutan mangrove terhadap peningkatan ekonomi; Kurangnya pengetahuan masyarakat sekitar lingkungan ekowisata hutan mangrove terkait pelestarian dan penjagaan hutan mangrove; Kurangnya informasi dan promosi yang terintegrasi oleh mitra POKDARWIS hutan mangrove 212. Kegiatan pengabdian kepada masyarakat dilakukan dengan tahap observasi awal melalui kuesioner pra kegiatan, dilanjutkan dengan tahap pelaksanaan dengan sosialisasi dan pelatihan, dan tahap selanjutnya melakukan evaluasi. Luaran yang dihasilkan dalam pengabdian kepada masyarakat ini adalah: Terbentuknya koperasi POKDARWIS hutan mangrove 212; Terbentuknya Kelompok Usaha Bersama (KUBE) dari UMKM masyarakat sekitar ekowisata mangrove; Adanya 3 produk kreatif berbahan dasar mangrove; Adanya reboisasi hutan mangrove yang akan di budidayakan di ekowisata hutan mangrove kampung sejahtera; Adanya website yang terintegrasi sebagai wadah promosi; dan 6) Adanya signboard sebagai media informasi.Kata kunci: ekowisata; berbasis masyarakat; hutan mangrove kampung sejahtera kota bengkulu